Sustainable Aquaculture: The Role of Probiotic Fortification In Enhancing Catfish Growth In Biofloc Aquaponics Technology - Dewi, Endah Rita Sulistya; Mufidah, Ratna; Rakhmawati, Reni; Ulfah, Maria; Khoiri, Nur; Wijaya, Angelica Tricia; Hudin, Noraine Salleh (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Catfish (Pangasius sp.) is a freshwater fish commodity that is widely cultivated in the Indonesian fisheries sector. The aim of this research was to determine the effect of fortification of liquid probiotics bioprisma and biogan on the protein and fat of catfish meat in the biofloc aquaponics technology. The catfish used in this study was 7-8 cm in size. The research was carried out using a completely randomized design (CRD) method with 3 treatments and 3 replications, the treatments were as follows: P0 = without addition of probiotics, P1 = addition of bioprisma probiotics 0.15 mL/l,5 L of water, P2 = addition of biogan probiotics 0,15 mL/l,5 L of water. The data obtained were then processed and calculated using ANOVA at a 95% confidence interval if a significant effect was found, then continued with Duncan's further test. This study indicates that the addition of probiotic to catfish culture media can affect body protein, body fat, and water quality environmental condition (ammonia, nitrite, nitrate, DO) of catfish. The addition of probiotics in the P1 (addition of bioprisma probiotics 0,15 mL/l ,5 L of water) gave the best effect in increasing the growth of catfish, 18,70% body protein and 8,73% body fat. The integration of biofloc with aquaponics technologies can eliminate geographical limitations and accelerate the urbanization of aquaculture.